Biological characteristics and pulp regeneration potential of stem cells from canine deciduous teeth compared with those of permanent teeth - S. M. Ziauddin; Misako Nakashima; Hideto Watanabe; Michiyo Tominaga; Koichiro Iohara (Stem Cell Research & Therapy, 2022)
Abstract Background Clinical studies have demonstrated that dental pulp stem cells isolated from permanent teeth (PT-DPSCs) are safe and efficacious for complete pulp regeneration in mature pulpectomized permanent teeth with complete apical closure. Moreover, dental pulp stem cells from deciduous teeth (DT-DPSCs) have also been shown to be useful for pulp regenerative cell therapy of injured immature permanent teeth. However, direct comparisons of the pulp regenerative potential of DT-DPSCs and PT-DPSCs from the same individual have not been performed. This study aimed to compare the differences in stem cell properties and pulp regenerative potential of DT-DPSCs and PT-DPSCs of identical origin. Methods DT-DPSCs and PT-DPSCs were isolated from the same individual dogs at 4 months and 9 months of age, respectively. The expression of cell surface antigen markers, proliferation and migration activities, and gene expression of stem cell markers, angiogenic/neurotrophic factors and senescence markers were compared. The effects of conditioned medium (CM) derived from these cells on cellular proliferation, migration, angiogenesis, neurite outgrowth and immunosuppression were also compared. Autologous transplantation of DT-DPSCs or PT-DPSCs together with G-CSF was performed to treat pulpectomized teeth in individual dogs. The vascularization and reinnervation of the regenerated pulp tissues were qualitatively and quantitatively compared between groups by histomorphometric analyses. Results The rates of positive CXCR4 and G-CSFR expression in DT-DPSCs were significantly higher than those in PT-DPSCs. DT-DPSCs migrated at a higher rate with/without G-CSF and exhibited increased expression of the stem cell markers Oct3/4 and CXCR4 and the angiogenic factor VEGF and decreased expression of the senescence marker p16 than PT-DPSCs. DT-DPSC-derived CM promoted increased cell proliferation, migration with G-CSF, and angiogenesis compared with PT-DPSC-derived CM; however, no difference was observed in neurite outgrowth or immunosuppression. The regenerated pulp tissues in the pulpectomized teeth were quantitatively and qualitatively similar between the DT-DPSCs and PT-DPSCs transplant groups. Conclusions These results demonstrated that DT-DPSCs could be a potential clinical alternative to PT-DPSCs for pulp regenerative therapy. DT-DPSCs can be preserved in an individual cell bank and used for potential future pulp regenerative therapy before the supply of an individual’s own sound discarded teeth has been exhausted.